Analysis of the Application and Benefits of Aircraft Electric Wheel Systems during Taxi and Take-Off - Shuang Sun; Yu Liao; Shuo Ding; Yinte Lei; Song Li; Zhijie Hu; Hualong Dong (International Transactions on Electrical Energy Systems)
An electric wheel hybrid power system is designed for driving a large single-aisle passenger aircraft during the take-off and ground taxi phases, which consists of an APU, an energy storage system, and a motor. In the taxi phase, the electric wheel hybrid power system works alone, and the turbofan engine does not work, reducing fuel consumption and pollution emissions. During the take-off rolling phase, the electric wheel hybrid power system and turbofan engine work together to reduce the thrust requirement of the turbofan engine. This article establishes an aircraft kinematic model, hybrid power system model, and a mechanical wheel model. The feasibility of the collaborative work of the electric wheels and the turbofan engines is verified by simulations. By utilizing the established hybrid system of electric motor wheels, the fuel consumption can be reduced, and the emissions of CO, HC, and NOX can also be diminished to varying degrees. The input of motor power leads to lower turbine inlet temperature, thereby enhancing the turbofan engine’s service life by approximately 4.3% and saving operational costs.